Conceptions about a?ectivity in teachers working in hospital classrooms in Chile - Contreras Salinas, Sylvia (2020)
This article describes the conceptions of affectivity in the speeches of teachers who work in a hospital classroom belonging to a public hospital in the Metropolitan Region in Chile are explored, considering it as a multidimensional experience, from which the teaching practice is configured. The methodology and procedures correspond to a qualitative approach, specifically, a case study. For this, the whole teaching team that attends children diagnosed with cancer was interviewed. The main findings indicate that the category affectivity is not visualized as a phenomenon that is theorized and recreated in the discourse of the teachers interviewed. Finally, it is concluded that it is necessary to advance in valuing and clarifying the affectivity put into play in the educational act.